Effects of unethical behavior among professionals in Klang Valley construction industry - Sarah Wong Woei Lynn,; Nur Ilya Farhana Md Noh,; Salihah Surol,; Zakiah Ahmad,; Ng, Jing Lin; Lee, Jin Chai; Deprizon Syamsunur,; Ramez Al-Ezzi Abduljalil Al-Mansob,; Ruzaimah Razman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Professionals are integral to the project. However, conflicts of interest among professional such as clients and contractors, project managers, architects play an important role in unethical practices that have an adverse effect in the construction industry. Therefore, this study aims to identify the effects of unethical issues that occur among the professionals in Klang Valley construction industry. The data collection has been conducted via questionnaire survey and has been analyzed using SPSS. Most respondents agree that “Delay of construction project” is the main effect of unethical behavior with a mean of 4.36 and SD= 0.848. When a project is delayed, it would cause major problems such as project abandonment, cost overrun, conflicts against parties and poor-quality works. This is because a project depends on the cost and time in order to be completed. Furthermore, a delayed project leads to a rushed project that will cause defective works. Frequent maintenance will be needed for repairing works, thus increasing the cost to bear in the project itself. Lastly, it is recommended that the timeframe for future studies should be increased to allow researchers to have sufficient time to collect more data in order to improve the accuracy and reliability of data collected.